ELECTRICAL ARC FLASH SAFETY DETECTION IN POWER DISTRIBUTION NETWORK - AMAKIRI OKILO FRIDAY; AGHAUKWU CELESTINE NONSO; SIMON ITA OKISAK (Journal of Engineering Studies and Research)
This paper seeks to investigate the safety issues surrounding Federal University of Petroleum Resources Effurun (FUPRE) distribution network and the steps taken by the management to ensure that all employee’ health and safety issues are protected. Using direct observation, data were collected while ETAP was used to analyze the system. According to our findings, the Admin Block has the highest total fault current with an arcing value of 11.197 A and a bolted fault of 15.490 A, followed by College of Science with an arcing value of 9.460 A and a bolted fault of 13.106 A. Bus 1 has the lowest arcing value of 0.735 A and a bolted fault of 0.735A but with the highest incident energy of 6.180 cal/cm2, followed by Admin Block with incident energy of 2.868, while Health Center and Hostel had the lowest incident energy of 0.194 cal/cm2 and 0.196 cal/cm2, respectively. Arc-Flash Hazards are classified into five Hazard Risk Categories by NFPA 70E, Standard for Electrical Safety in the Workplace which range from category A-C from the findings. This has helped to shed more light on the safety detection and control practices in workplace. This work adopted the incident energy analysis method during the investigation of the FUPRE distribution network. This analysis also showed the effectiveness of FUPRE distribution network in terms of health and safety practices.